Does the long-term precipitation variations and dry-wet conditions exist in the arid areas? A case study from China. (10th June 2019) - Liu, Yi; Chen, Shujun; Sun, Huaiwei; Gui, Dongwei; Xue, Jie; Lei, Jiaqiang; Zeng, Xiaofan; Lv, Guanghui
Abstract: The detailed precipitation characteristics is required for the investigation of regional hydrological processes, precipitation related disasters, and water resources management. Quantifying and understanding the precipitation change in arid area are crucial for prediction of its future and avoiding disasters. In this study, it was investigated the precipitation concentration, and its variability along with the linkage of global large-scale circulation anomalies in Xinjiang between 1960 and 2016. Using meteorological data from 54 weather stations coupling with atmospheric circulation indices, several precipitation indices were used as standard measures for determining the basic characteristics of floods and droughts. Results showed that the characteristics of the precipitation concentration feature were identified by two precipitation indices: precipitation concentration degree (PCD) and precipitation concentration period (PCP). The PCD value has decreased in recent years, which illustrates the characteristics of drought. The values of the precipitation concentration index (PCI) that indicated extreme precipitation ranged from 9 to 20 in 57 years and exhibited a significant decreasing trend in 1960–2016. However, an increasing precipitation condition can be observed through the monthly standardized precipitation index (SPI), which indicates that drought–flood abrupt alternation will be more frequent and the abrupt change should be noticed in recent years. It is found to be suitable to use the long-cycle drought–flood abrupt alternation index (LDFAI) to investigate the characteristics of drought–flood abrupt alternation during summers. Further investigations on the linkage between drought–flood abrupt alternation and atmospheric circulation indices showed that the time delay of LDFAI after an atmospheric anomaly will be 1–4 months. The results of this study will help mitigate and regulate the precipitation related problems in arid area, as well as in other regions.